Social impact assessment (SIA): a review of SIA procedure in Malaysia - Hassan, Mohammad Mujaheed (The International Journal of Social Sciences and Humanities Invention, 2018)
Social Impact Assessment (SIA) essentially is an individual report or a subfield of an Environmental Impact Assessment (EIA). It is demarcated as the social sciences required in developing a knowledge base to provide a systematic assessment, in advance of the impacts, on the day-today quality of life of persons and communities whose environment is affected by a proposed project, plan or policy change. SIA is a platform for diverse groups and people in a community to voices out their need and concern. SIA are the 'people impacts' of development actions. Social impact assessments focus on the human dimension of environments, and seek to identify the impacts on people who benefits and who loses. New provision has been enforced in January 2017 to the Malaysia SIA procedure. Therefore the objective of this paper is to review the new provision and procedure of SIA enforcement in Malaysia.